- Pelaksanaan Prinsip Kehati-hatian Bank Permata Dalam Pemberian Kredit - Abdill Hannandi; Keumala, Dinda (Reformasi Hukum Trisakti, 2023)
As in the case of the judgement no. 435.Pid.Sus/2020/PT. DKI between Bank Permata and the company's debtor and the debtor's negligence in meeting his payment obligations, banks are required to apply the precautionary principle when conducting credit activities. The issue is whether Bank Permata adhered to the precautionary principle when providing credit to businesses that were debtors in the case of decision no. 435/Pid.Sus/2020/PT.DKI and whether the judge's considerations were compliant with banking law laws. The research is normative juridical in nature, descriptive, and involves data through literature review, qualitative analysis, and deductive conclusion. Research findings, and discussion; Bank Permata in providing credit approval to debtors does not fully use the precautionary principle such as inaccuracies in 5C analysis, does not verify documents and field checks. In the decision at the appeal level, banking regulations such as Bank Indonesia Regulation number 14/27/PBI/2012 concerning the Application of Anti-Money Laundering and Prevention of Terrorism Funding Programs for Commercial Banks are not considered by the judge at the High Court. The conclusion is that Bank Permata did not carry out a thorough 5C analysis and also did not verify documents, physical checks at the debtor's business location, and trade checking procedures for PT. MJPL.